Domesticating cleaner cookstoves for improved respiratory health: Using approaches from the sanitation sector to explore the adoption and sustained use of improved cooking technologies in Nepal. (September 2022) - Jewitt, Sarah; Smallman-Raynor, Matthew; K C, Binaya; Robinson, Benjamin; Adhikari, Puspanjali; Evans, Catrin; Karmacharya, Biraj Man; Bolton, Charlotte E.; Hall, Ian P.
Abstract: Drawing on village-based data from Nepal, this paper explores the transferability of the Integrated Behavioural Model for Water, Sanitation and Hygiene (IBM-WASH) to the clean cooking sector and its potential to elucidate how barriers to improved cookstove adoption and sustained use intersect at different scales. The paper also explores the potential of IBM-WASH, behaviour settings theory and domestication analysis to collectively inform effective behaviour change techniques and interventions that promote both adoption and sustained use of health-promoting technologies. Information on cookstove use in the community since 2012 enables valuable insights to be gained on how kitchen settings and associated cooking behaviour were re-configured as homes and stoves were re-built following the April 2015 earthquake. The methodological approach comprised of semi-structured interviews, focus group discussions, direct observation and household surveys. The findings indicated that the IBM-WASH framework translated well to the improved cookstove sector, capturing key influences on clean cooking transitions across the model's three dimensions (context, psychosocial and technology) at all five levels. Understandings gained from utilising IBM-WASH were enhanced – especially at the individual and habitual levels – by domestication analysis and settings theory which elucidated how different cooking technologies were incorporated (or not) within physical structures, everyday lives and routine behaviour. The paper concludes that this combination of approaches has potential applicability for initiatives seeking to promote improved environmental health at community-wide scales. Highlights: Transferability of IBM-WASH to the cookstove sector is explored for the first time. Data from post-earthquake Nepal is used to test this transferability. We demonstrate that the framework translates well to the cookstove sector. Findings from IBM-WASH are enhanced by domestication analysis and settings theory. This combination of approaches has broader applicability for health initiatives.